Unidimensional Measurement May Evaluate Target Lymph Nodal Response After Induction Chemotherapy for Nasopharyngeal Carcinoma. Issue 9 (March 2016) - Chen, Chuanben; Zhang, Mingwei; Xu, Yuanji; Yue, Qiuyuan; Bai, Penggang; Zhou, Lin; Xiao, Youping; Zheng, Dechun; Lin, Kongqi; Qiu, Sufang; Chen, Yunbin; Pan, Jianji
Abstract : Abstract: The aim of the study was to evaluate whether short axis and long axis on axial and coronal magnetic resonance imaging planes would reflect the tumor burden or alteration in size after induction chemotherapy in nasopharyngeal carcinoma. Patients with pathologically confirmed nasopharyngeal carcinoma (n = 37) with at least 1 positive cervical lymph node (axial short axis ≥15 mm) were consecutively enrolled in this prospective study. Lymph nodal measurements were performed along its short axis and long axis in both axial and coronal magnetic resonance imaging planes at diagnosis and after 2 cycles of induction chemotherapy. In addition, lymph nodal volumes were automatically calculated in 3D treatment-planning system, which were used as reference standard. Student's t test or nonparametric Mann–Whitney U test was used to compare the continuous quantitative variables. Meanwhile, the κ statistic and McNemar's test were used to evaluate the degree of agreement and discordance in response categorization among different measurements. Axial short axis was significantly associated with volumes at diagnosis ( P < 0.001). A good agreement (κ=0.583) was found between axial short axis and volumetric criteria. However, the inconsistent lymph nodal shrinkage in 4 directions was observed. Axial short-axis shrinking was more rapid than the other 3 parameters. Interestingly, when utilizing the alternative planes for unidimensional measurements to assess tumor response, coronal short-axis showed the best concordance (κ=0.792) to the volumes. Axial short axis may effectively reflect tumor burden or change in tumor size in the assessment of target lymph nodal response after induction chemotherapy for nasopharyngeal carcinoma. However, it should be noted that axial short axis may amplify the therapeutic response. In addition, the role of coronal short axis in the assessment of tumor response needs further evaluation.